ANALISIS PENGARUH ROA, NPL, SUKU BUNGA BANK INDONESIA (BI RATE), DAN PERTUMBUHAN EKONOMI (GDP) TERHADAP PENYALURAN KREDIT KPR (Studi Pada Bank Persero Periode 2011-2015) - Djati, Stefano Rahadian Rama; Kamal, Mustafa (Faculty of Economics and Business Diponegoro University, 2017)
There are several factors that affect the world banks to extend home mortgages to the public. The purpose of this study was to analyze the factors that influence the distribution of home loans at state banks period 2011-2015. Home loans in this study is the dependent variable. There are four independent variables used in this study, Return on Assets (ROA), Non Performing Loan (NPL), interest rate of Bank Indonesia (BI Rate) and Economic Growth (GDP).The data used in this study was 60 during the period 2011-2015. In sampling this study using purposive sampling technique, so that there are three samples of four state banks in Indonesia. Data were processed using linear regression techniques using SPSSBased on regression analysis showed that ROA and credit growth (GDP) negatively, while variable Non Performing Loan (NPL) and the variable BI Rate no significant effect on mortgage loans. ROA is the most dominant variable (-0.495) in influencing mortgage loans.